Optimization of Rosenbrock function usingGenetic Algorithm (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, Optimization is the most interesting problems to be studied. It is a process ofselecting the best alternative among a given set of options. In the past few decades, a lot ofoptimization algorithms came into existence to solve NP Hard problems. Genetic Algorithm is one ofthepopulations based meta-heuristic to solve such problems. Different benchmark functions areavailable to test the performance ofoptimization algorithms. Rosenbrock function is a popular testproblem for optimization based algorithms. This paper presents experimental results on optimizationof Rosenbrock function used for performance evaluation of Genetic Algorithm.